Adsorption of Phenol and Phenol Derivatives on Pure and Modified Kaolinite - Yildiz, A.; Gur, A. (Asian Journal of Chemistry, 2010)
In the present work, pure kaolinite and that modified by HNO3, EDTA and ☐DTMA, were used as the adsorbents.The changes on the surfaces were studied by IR spectroscopy. The adsorption of solutions of phenol and phenol derivatives in alcohol on these adsorbents was examined by means of gas-chromatography. As a result of these examinations, it was seen that the adsorption capacities of the clay-organic complexes (kaolinite-EDTA and kaolinite- HDTMA) were higher than pure kaolinite and kaolinite-HNO3.